Comparison between two different doses of Norepinephrine infusion for preventing post spinal Anesthesia Hypotension during Cesarean section - Bhattarai, Rupak; Yadav, Amarendra Kumar; Shah, Parasmani; Sharma, Prabin (Birat Journal of Health Sciences, 2023)
Introduction:  Post spinal maternal hypotension is common complication during cesarean section. Norepinephrine is a vasopressor recently used in obstetrics anesthesia. However, there are less data available regarding its optimal dose.Objective: The main objective of this study is to compare two doses of infusion of norepinephrine for post spinal hypotension during cesarean delivery.Methodology: A prospective, randomized, double blinded study on full term pregnant patient scheduled for elective cesarean delivery. The infusion of Norepinephrine started after spinal anesthesia after patient randomly divided into two groups. Group A received norepinephrine infusion rate of 0.025ug/kg/min and Group B received at rate of 0.050ug/kg/min. The norepinephrine was continued till 5 minutes after the delivery of fetus and subsequently stopped. These two groups were compared with systolic blood pressure, mean arterial pressure, heart rate, intraoperative hypotensive episodes, Nausea and Vomiting, tachycardia and neonatal outcomes.Results:  Systolic blood pressure and mean arterial pressure was higher in group B when compared with group A at all time intervals intraoperatively. The minimum systolic blood pressure and mean arterial blood pressure in group A were 91.61±8.76 and 59.8±5.29 and group B were 90.67±1.21 and 65±3.46 respectively. No significant difference in heart rate between the two groups. In 0.025ug/kg/min group had 23 (46%) hypotensive episode whereas in 0.050ug/kg/min group had 6 (12%) hypotensive episodes (p